Pemanfaatan Teknologi Cloud Computing dalam Pembelajaran Informatika di SMK - Purnama, Bayu Rizkhy Candra; Liantoni, Febri; Maryanti (Universitas Sebelas Maret, 2024)
Along with the development of information and communication technology, the use of cloud computing technology in education has become increasingly important. This study aims to explore the impact of using Google Forms, Quizizz, and Wordwall in informatics learning at vocational high schools (SMK). The method used is qualitative, with data obtained through interviews and observations. Observations were conducted when teachers used Google Forms to collect student responses, as well as Quizizz and Wordwall for pretests and post-tests. The results show that the use of cloud computing technology increases the efficiency and effectiveness of learning, as well as the quality of student learning outcomes. The conclusion of this study is that cloud computing technology can have a significant positive impact on informatics learning at SMK. The contribution of this research is to provide a basis for further development and application of digital technology in education.